Desenvolvimento profissional docente na perspecitiva da participação sindical: diálogos propositivos para qualificação do plano de carreira dos professores municipais de Santa Maria/RS - Najar, Martha Izabel Pauler (2019)
This research is linked to the Postgraduate Program in Public Policy and Educational Management, from the Professional Master Degree, of Federal University of Santa Maria (UFSM) whose problem was how the Career Plan of municipal teachers from Santa Maria / RS contributes to the professional development in the context of continuing education in order to qualify the activity hour also how the union can be a protagonist in this process, it had as purpose understand how the Career Plan of the Magisterium of the Municipal Education Network from Santa Maria / RS can contribute to the professional developmen from the right of activity hour, as well as the union can be protagonist in this process. To the aims of this study it was sought in (NÓVOA, 1991, 1995; 2009), (IMBERNÓN, 2011) (GARCIA, 1999) (SCHÖN, 1995) and others besides the Legal Marks based on the Brazilian Federal Constitution of 1988. The methodological approach was based on Collaborative Research (IBIAPINA, 2018) with construction of data from Dialogic Circles (HENZ, 2015) and data analysis from the perspective of Hermeneutics (GADAMER, 1999), as well as the use of documentary analysis. The process of constitution of the subject from a formative action in the collective, professional and organizational dimensions, with the perspective of union participation, establishes for the union the possibility of promoting debate about professional performance and the [re] knowledge and defense of Career plan. The relevance of this research is assumed by the complexity of the subject, once, the processes of construction of teachers career plans are important mechanisms for guaranteeing professional valorization. So, the questions about this research concerned about the importance of the study and defense of Career Plans as a referential instrument for the struggle of teachers in the effects of professional valorization and guarantee of rights, whose product was the construction of an Agenda of Proposals for Devenlopment Professional research stimulation for Municipal teachers from Santa Maria RS considering the protection of Law 11.738 / 08, anchored in the Parecer CNE / CEB 18/2 in order that the teacher be valued with decent wages, space-time for training, preferentially into their contexts of action promoting a culture of researching teacher in an attitude of reflection in practice and about practice.